Short‐term effect of outdoor mould spore exposure on prescribed allergy medication sales in Central France. Issue 7 (17th May 2018) - Caillaud, D.; Cheriaux, M.; Martin, S.; Ségala, C.; Dupuy, N.; Evrard, B.; Thibaudon, M.
Summary: Background: Outdoor moulds are classically associated with exacerbations of asthma. Objective: The aim of this paper was to examine nasal allergy morbidity by studying the short‐term relationship between mould spore exposure and daily sales of reimbursable anti‐allergic treatment in central France. Methods: The relationship between daily changes in mould concentrations and daily sales obtained from the national healthcare database was analysed with generalized additive models, taking into account confounding factors such as air pollution, weather conditions, pollen counts, and days of the week. Results: During the study, the average total yearly number of treated people was around 10 000 over approximately 230 000 surveyed. The relative risk (95% CI confidence interval) of sales of oral antihistamines with topical treatment associated with an interquartile increase in mould concentration was significant for Cladosporium 1.079 [1.019‐1.142] and Aspergillus‐Penicillium ( Asp‐Pen) 1.051 [1.021‐1.082] in the whole population. When the influence of age and sex was considered, the relationship was significant only in male children aged 0‐12 years and those aged between 13 and 49 years for Cladosporium: 1.256 [1.081‐1.460] and 1.151 [1.063‐1.245], respectively. The relationship was also significant for Asp‐Pen : 1.038 [1.003‐1.075] for those aged between 13 and 49 years and 1.056 [1.007‐1.108] for adults over 50 years of age. Conclusion: The association between prescribed daily sales of oral antihistamines with topical treatment sales is associated with temporal changes to Cladosporium and Aspergillus ‐ Penicillium in the whole population. When the influence of age and sex was considered, these two moulds contributed to prescribed medication sales only in the male general population.